The pencil - Ahlberg, Allan; Ingman, Bruce, 1963- (Cambridge, Mass. : Candlewick Press, 2008)
A lonely pencil timidly draws a boy, a dog, and other items but soon faces a problem as his creations begin demanding changes, and when he draws an eraser to make them happy, the real trouble begins.
A Junior Library Guild selection
Keywords: Pencils -- Juvenile fiction; Drawing -- Juvenile fiction; Loneliness -- Juvenile fiction; Pencils -- Fiction; Drawing -- Fiction; Loneliness -- Fiction